2019
DOI: 10.1111/ppa.13100
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of prophage and historical perspectives associated with the dissemination of huanglongbing in mainland China

Abstract: Huanglongbing (HLB), associated with a non‐culturable bacterium ‘Candidatus Liberibacter asiaticus’ (CLas), is a highly destructive citrus disease with a long but poorly documented history in China. No effective treatment for HLB is available. The identification of new prophages in abundant CLas genomic sequence data provides new insights into both the diversity of CLas strains and HLB management. In this study, CLas populations from nine provinces were surveyed for the presence of prophage. Two major prophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
(27 reference statements)
2
9
1
Order By: Relevance
“…This can be explained by the introduction of Las with budwood or seedlings and transmissions by the insect vector ( D. citri ), providing additional evidence for a possible introduction of Las from neighbouring provinces. Altitude is evidently an important factor influencing Las diversity in the high altitude regions (Yunnan and Guizhou in this study), which has also been partly confirmed by other studies (Fu et al, 2020; Li et al, 2019; Xu et al, 2014). The electrophoresis type at all three types of loci was relatively simple in the Las population of Jiangxi.…”
Section: Discussionsupporting
confidence: 90%
“…This can be explained by the introduction of Las with budwood or seedlings and transmissions by the insect vector ( D. citri ), providing additional evidence for a possible introduction of Las from neighbouring provinces. Altitude is evidently an important factor influencing Las diversity in the high altitude regions (Yunnan and Guizhou in this study), which has also been partly confirmed by other studies (Fu et al, 2020; Li et al, 2019; Xu et al, 2014). The electrophoresis type at all three types of loci was relatively simple in the Las population of Jiangxi.…”
Section: Discussionsupporting
confidence: 90%
“…Prophage genes have been demonstrated to be the better markers for differentiating the C Las strains from different geographic origins ( 20 , 21 , 23 ). The origin of prophages from Liberibacters associated with plants is not homologous ( 22 , 32 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations within these analyzed nonprophage regions were low and could hardly distinguish closely related C Las. C Las does have several hypervariable prophage regions ( 19 to 22 ). However, the prophage varies from 0 to 2 copies in different C Las isolates and could only distinguish partial C Las isolates ( 23 to 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these two known prophages there could have been other unknown types of prophage or no prophage at all. (Fu et al 2019). Bacteriophages provide insight into a virulence mechanism of 'Ca.…”
Section: Discussionmentioning
confidence: 99%